2013
DOI: 10.1002/ajim.22187
|View full text |Cite
|
Sign up to set email alerts
|

More than training: Community‐based participatory research to reduce injuries among hispanic construction workers

Abstract: This study provides evidence for successful implementation of a training intervention for low wage, low literacy Hispanic construction workers using a community-based participatory research approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 37 publications
(45 reference statements)
1
57
0
1
Order By: Relevance
“…13,14,23,[26][27][28] Although one prior report investigated working conditions among construction workers in the state of Texas and one injury prevention community-based participatory research study was conducted among Hispanic construction workers, to our knowledge, there are no published studies documenting self-reported on-the-job injuries among LDLs in Texas. 29,30 In this study, we (1) describe injuries reported by day laborers in Houston, Texas, (2) explore the extent to which demographic and occupational risk factors predict self-reported onthe-job injuries, and (3) explore whether summative exposure measures for the total job types, total job conditions, and total PPE predict self-reported occupational injuries.…”
Section: Study Aimsmentioning
confidence: 99%
“…13,14,23,[26][27][28] Although one prior report investigated working conditions among construction workers in the state of Texas and one injury prevention community-based participatory research study was conducted among Hispanic construction workers, to our knowledge, there are no published studies documenting self-reported on-the-job injuries among LDLs in Texas. 29,30 In this study, we (1) describe injuries reported by day laborers in Houston, Texas, (2) explore the extent to which demographic and occupational risk factors predict self-reported onthe-job injuries, and (3) explore whether summative exposure measures for the total job types, total job conditions, and total PPE predict self-reported occupational injuries.…”
Section: Study Aimsmentioning
confidence: 99%
“…The type of construction work varied, from specific trades (e.g., carpentry, roofing, tiling, concrete, floor laying) to larger scale industries (e.g., metal/steel/aluminium work, stone quarry, railways). Six studies were conducted in the USA (Becker et al, 2001;Darragh et al, 2004;Forst et al, 2013;Kerr et al, 2007;Lusk et al, 1999;Sokas et al, 2009), three in Denmark (Kines et al, 2013(Kines et al, , 2010Spangenberg et al, 2002), two in Italy (Bena et al, 2009;Mancini et al, 2005), and one each in Hong Kong (Lingard and Rowlinson, 1997), India (Adams et al, 2013), Spain (Lopez-Ruiz et al, 2013), and Finland (Laitinen and Päivärinta, 2010).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Two studies used a pre-post design with a control group but were not classified as RCTs due to non-random assignment to conditions (Becker et al, 2001) or comparison with non-matched convenience samples (Mancini et al, 2005). Two studies used a pre-post design with no control group (Forst et al, 2013;Sokas et al, 2009); three studies used an interrupted time-series design with (Laitinen and Päivärinta, 2010) or without a control group (Darragh et al, 2004;Spangenberg et al, 2002); and two studies used a mixed-approach including both pre-post and time-series analyses with (Lopez-Ruiz et al, 2013) or without a control group (Bena et al, 2009). The final study employed a within-groups design where four different behaviours were targeted in a staggered fashion and the same group of participants served as the intervention and control groups (Lingard and Rowlinson, 1997).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations